Factors affecting employees' performance at Hospital Universiti Sains Malaysia (HUSM) Kelantan / Fauziannie Mail - Mail, Fauziannie (2015)
This study was conducted to investigate the impact of workload, work environment, supervisory communication, reward factor and technology advancement on employee performance. Researcher interference in this research was very limited and done under natural work environment. For this research, 140 employees of Hospital Universiti Sains Malaysia (HUSM) were taken as respondent. Majority of the respondents were female. Based on the findings, reliability analysis for all the variables were considered as good because they obtained 0.7 and above. As for correlation analysis, technology advancement does not significantly correlated to employee performance. From hypothesis testing result, two from five hypotheses were contributed to employee performance and accepted. They were supervisory communication and technology advancement.